Effect of feed supplementation and early weaning on postpartum reproductive performance of crossbred cows in the tropics - Camacho S., José (2009)
The effect of feed supplementation and temporary weaning in 46 crossbred Bos taurus x Bos indicus cows on the resumption of post partum ovarian activity was evaluated. Animals were distributed in three treatments: T1, Control, cows without supplementation + calf at foot; T2, Feed supplementation + calf at foot and temporary weaning (48 h) at 60 days post partum; and T3, Feed supplementation + calf at foot. Supplement consisted of 3 kg/cow/day from calving till 60 days post partum. Blood samples were collected twice a week since week 3 till week 16 post partum for the determination of progesterone levels as indicator of the resumption of ovarian activity. The interval calving-first ovulation was 70.6, 56.4, and 57.8 days for cows that ovulate within the first 12 weeks after calving in groups T1, T2, and T3 respectively. The 31.3, 73.3, and 66.7% of cows in each treatment group ovulate within that period. It is concluded that feed supplementation and temporary weaning contribute in improving post partum reproductive performance in crossbred cattle in the Peruvian tropics.